2020
DOI: 10.1177/2325967120960107
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fatty Infiltration of the Teres Minor Negatively Affects Postoperative Outcomes in Patients With Rotator Cuff Pathology

Abstract: Background: The teres minor is a critical component of the rotator cuff and serves as one of the few external rotators of the humerus. Information is lacking regarding the effect of teres minor atrophy in isolation and in the setting of concomitant full-thickness rotator cuff tears on outcomes in patients undergoing rotator cuff surgery. Purpose: To investigate the effect of preoperative teres minor fatty infiltration on postoperative clinical outcomes in patients with and without full-thickness rotator cuff p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Recent literature has indicated varying patient outcomes with and without teres minor atrophy after rotator cuff repair. In a cohort of 21 patients who underwent repair of full-thickness rotator cuff tears, any degree of preoperative teres minor atrophy (Goutallier grade 1-4) 37 was associated with significantly lower postoperative American Shoulder and Elbow Surgeons (ASES) (48.9 vs. 83.5, p 5 0.0056) and inferior QuickDASH (46.5 vs. 13.1, p 50.0042) scores at a 2year follow-up compared with patients without teres minor atrophy 18 . By contrast, Kim et al 38 evaluated a cohort of 51 patients with preoperative teres minor fatty infiltration of a cohort of 816 patients who underwent rotator cuff repair and demonstrated that fatty infiltration of the teres minor did not affect the visual anolog scale (VAS) (1.5 vs. 1.9, p 5 0.367), Simple Shoulder Test (11 vs. 10, p 5 0.110), ASES (89.1 vs. 87.1, p 50.443), external rotation range of motion (36 vs. 34, p 5 0.744), or strength (5/5 vs. 5/5, p 50.719) at 1 year.…”
Section: Rotator Cuff Pathologymentioning
confidence: 94%
See 1 more Smart Citation
“…Recent literature has indicated varying patient outcomes with and without teres minor atrophy after rotator cuff repair. In a cohort of 21 patients who underwent repair of full-thickness rotator cuff tears, any degree of preoperative teres minor atrophy (Goutallier grade 1-4) 37 was associated with significantly lower postoperative American Shoulder and Elbow Surgeons (ASES) (48.9 vs. 83.5, p 5 0.0056) and inferior QuickDASH (46.5 vs. 13.1, p 50.0042) scores at a 2year follow-up compared with patients without teres minor atrophy 18 . By contrast, Kim et al 38 evaluated a cohort of 51 patients with preoperative teres minor fatty infiltration of a cohort of 816 patients who underwent rotator cuff repair and demonstrated that fatty infiltration of the teres minor did not affect the visual anolog scale (VAS) (1.5 vs. 1.9, p 5 0.367), Simple Shoulder Test (11 vs. 10, p 5 0.110), ASES (89.1 vs. 87.1, p 50.443), external rotation range of motion (36 vs. 34, p 5 0.744), or strength (5/5 vs. 5/5, p 50.719) at 1 year.…”
Section: Rotator Cuff Pathologymentioning
confidence: 94%
“…2). The amount of fatty infiltration and the ability of clinicians to recognize it on imaging are important as it may correlate with improved function after rotator cuff surgery or reverse shoulder replacement [17][18][19] .…”
mentioning
confidence: 99%
“…Teres minor was for a long time an under-investigated segment of the rotator cuff ( 42 ) until the first long-term outcome study on RSA pointed out its importance ( 18 ). Although its atrophy and fatty infiltration on CT or MR imaging is rare ( 43 ), it has been reported to have an impact on rotator cuff repair and RSA outcomes ( 44 ), as well as outcomes of latissimus dorsi tendon transfers ( 45 ). As shown by Collin, high-grade fatty infiltration of teres minor in massive rotator cuff tears is associated with both AFE pseudoparalysis and ER pseudoparalysis ( 3 ).…”
Section: Pathobiomechanicsmentioning
confidence: 99%